2017
DOI: 10.1096/fj.201601050rr
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the phosphatase‐transcription activator EYA1 by protein arginine methyltransferase 1: mechanistic, functional, and structural studies

Abstract: The eyes absent (EYA) family proteins are conserved transcriptional coactivators with intrinsic protein phosphatase activity. They play an essential role in the development of various organs in metazoans. These functions are associated with a unique combination of phosphatase and transactivation activities. However, it remains poorly understood how these activities and the consequent biologic functions of EYA are regulated. Here, we demonstrate that 2 conserved arginine residues, R304 and R306, of EYA1 are ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…All other known HAD protein phosphatases dephosphorylate Ser/Thr residues, while Eya targets phosphorylated Tyr 46 . Schor and colleagues recently demonstrated that methylation of the highly conserved residues R304 and R306 in Eya1 is essential for its Tyr phosphatase activity, revealing a possible mechanism through which the Tyr phosphatase activity of Eya can be regulated 47 .…”
Section: The Tyr Phosphatase Activity Of Eyamentioning
confidence: 99%
“…All other known HAD protein phosphatases dephosphorylate Ser/Thr residues, while Eya targets phosphorylated Tyr 46 . Schor and colleagues recently demonstrated that methylation of the highly conserved residues R304 and R306 in Eya1 is essential for its Tyr phosphatase activity, revealing a possible mechanism through which the Tyr phosphatase activity of Eya can be regulated 47 .…”
Section: The Tyr Phosphatase Activity Of Eyamentioning
confidence: 99%